Networking scheme of multi manufacturers' equipment in VoLTE domain - Wei QIU; Zheng, FENG; Qian WU (Dianxin kexue)
The deployment of VoLTE involves all aspects of the network, among them the construction of IMS core network is more crucial. The IMS networking solutions of different manufacturers' devices after the deployment of VoLTE were studied and many recommendations were proposed, which would provide reference for the deployment of VoLTE commercial network.